2002
DOI: 10.1007/s00520-001-0328-x
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of a catheter-related right atrial thrombosis with recombinant tissue plasminogen activator and heparin

Abstract: Deep venous thrombosis is a possible complication of indwelling central venous catheters (CVC), with an incidence as high as 61%. We report a case of successful thrombolysis of a CVC-related right atrial thrombus in a pediatric cancer patient with recombinant human tissue plasminogen activator (0.1 mg/kg per h for 12 h) and heparin (10 IU/kg per h for 24 h) administered for 6 days. Daily echocardiographic examination showed progressive lysis of the thrombus. The thrombolytic treatment was associated with mild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Figure 2 [2] Case report 1 Road traffic accident victim on TPN Korones et al [13] Prospective cohort 13 Cancer Marsh et al [14] Prospective 1 Prematurity, bowel perforation on TPN Bilginer et al [15] Case report 1 Renal transplant Torres-Validvesso et al [16] Case report 1 Prematurity Giuffrè et al [17] Case report 2 Prematurity Giannoulia-Karadana et al [18] Case report 2 Wilms tumor Dollery et al [19] Retrospective 5 Gut failure on TPN Asante-Korang et al [20] Case report 1 Tricuspid atresis, post-Fontan procedure Ross et al [21] Retrospective 16 Prematurity and cancer Sharrat et al [22] Case reports 1 Post-Fontan procedure Ozimek et al [23] Case report 1 Non-Hodgkins lymphoma De Schepper et al [24] Case reports 2 Prematurity, on TPN Hollingsed et al [25] Case report 1 Sickle cell anemia, fungal septicemia Riggs et al [26] Case reports 4 Prematurity, TPN, Wilms tumor Ká dá r et al [27] Case report 6 Postcardiac surgery Delaplane et al [28] Case report 1 Prematurity, on TPN Marsh et al [29] Case reports 2 Prematurity, septicemia Mahony et al [30] Case reports 2 Gastroschisis, TPN, and liver tumor Graham and Gumbiner [31] Case report 1 Prematurity, gastroschisis Sadiq et al [32] Case series 10 Prematurity and TPN Cesaro et al [33] Case report 1 Non-Hodgkins lymphoma Kingdon et al [34] Case reports 2 Renal failure on dialysis Paut et al [35] Case report 1 Trauma on TPN Moukarzel et al [36] Retrospective 6 All on TPN Teitelbaum et al [37] Case report 1 Failure to thrive, vomiting, on TPN RAT, right atrial thrombosis; TPN, total parenteral nutrition. …”
Section: Underlying Medical Conditionmentioning
confidence: 99%
“…Figure 2 [2] Case report 1 Road traffic accident victim on TPN Korones et al [13] Prospective cohort 13 Cancer Marsh et al [14] Prospective 1 Prematurity, bowel perforation on TPN Bilginer et al [15] Case report 1 Renal transplant Torres-Validvesso et al [16] Case report 1 Prematurity Giuffrè et al [17] Case report 2 Prematurity Giannoulia-Karadana et al [18] Case report 2 Wilms tumor Dollery et al [19] Retrospective 5 Gut failure on TPN Asante-Korang et al [20] Case report 1 Tricuspid atresis, post-Fontan procedure Ross et al [21] Retrospective 16 Prematurity and cancer Sharrat et al [22] Case reports 1 Post-Fontan procedure Ozimek et al [23] Case report 1 Non-Hodgkins lymphoma De Schepper et al [24] Case reports 2 Prematurity, on TPN Hollingsed et al [25] Case report 1 Sickle cell anemia, fungal septicemia Riggs et al [26] Case reports 4 Prematurity, TPN, Wilms tumor Ká dá r et al [27] Case report 6 Postcardiac surgery Delaplane et al [28] Case report 1 Prematurity, on TPN Marsh et al [29] Case reports 2 Prematurity, septicemia Mahony et al [30] Case reports 2 Gastroschisis, TPN, and liver tumor Graham and Gumbiner [31] Case report 1 Prematurity, gastroschisis Sadiq et al [32] Case series 10 Prematurity and TPN Cesaro et al [33] Case report 1 Non-Hodgkins lymphoma Kingdon et al [34] Case reports 2 Renal failure on dialysis Paut et al [35] Case report 1 Trauma on TPN Moukarzel et al [36] Retrospective 6 All on TPN Teitelbaum et al [37] Case report 1 Failure to thrive, vomiting, on TPN RAT, right atrial thrombosis; TPN, total parenteral nutrition. …”
Section: Underlying Medical Conditionmentioning
confidence: 99%
“…Patients were most frequently treated with systemic thrombolysis monotherapy, although one case report described successful outcomes with concurrent tPA and intravenous heparin infusions. 11 The overall incidence of hemorrhagic complications described in the case reports was low, but one patient who received monotherapy with systemic tPA developed an intracerebral bleed with subsequent persistent neurologic impairment. 6 There is a paucity of data regarding the use of localized thrombolytic administration, or CDT, for treatment of right atrial thrombi.…”
Section: Discussionmentioning
confidence: 91%
“…However, improved survival with thrombolysis compared with heparin therapy or embolectomy was shown (odds ratio for mortality 0.33, 95% confidence interval 0.11–0.98) . Numerous case reports describing the successful treatment of right atrial thrombi with systemic thrombolysis have been described in both adult and pediatricpatients. Patients were most frequently treated with systemic thrombolysis monotherapy, although one case report described successful outcomes with concurrent tPA and intravenous heparin infusions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A completely dissolved right atrial thrombus case without side effects was reported by Adamovich et al in a neonate after 5 days' with infusion of urokinase and heparin (128). Cesaro et al reported on a successful pediatric case that was treated with recombinant tissue plasminogen activator (rt-PA) and heparin for 6 days without significant side effects (129). Korones et al favoured conservative management for small-sized thrombus with no intervention but close follow up for evidence of growth in size is warranted.…”
Section: B Medical Managementmentioning
confidence: 99%